Rooting carbon dioxide removal research in the social sciences. Issue 5 (6th October 2020) - Dowell, Glen; Niederdeppe, Jeff; Vanucchi, Jamie; Dogan, Timur; Donaghy, Kieran; Jacobson, Rory; Mahowald, Natalie; Milstein, Mark; Zelikova, T. Jane
Abstract : Reports from a variety of bodies have highlighted the role that carbon dioxide removal (CDR) technologies and practices must play in order to try to avoid the worst effects of anthropogenic climate change. Research into the feasibility of these technologies is primarily undertaken by scholars in the natural sciences, yet, as we argue in this commentary, there is great value in collaboration between these scholars and their colleagues in the social sciences. Spurred by this belief, in 2019, a university and a non-profit organization organized and hosted a workshop in Washington, DC, intended to bring natural and physical scientists, technology developers, policy professionals and social scientists together to explore how to better integrate social science knowledge into the field of CDR research. The workshop sought to build interdisciplinary collaborations across CDR topics, draft new social science research questions and integrate and exchange disciplinary-specific terminology. But a snowstorm kept many social scientists who had organized the conference from making the trip in person. The workshop went on without them and organizers did the best they could to include the team remotely, but in the age before daily video calls, remote participation was not as successful as organizers had hoped. And thus, a workshop that was supposed to focus on social science integration moved on, without many of the social scientists who organized the event. The social scientists in the room were supposed to form the dominant voice but with so many stuck in a snow storm, the balance of expertise shifted, as it often does when social scientists collaborate with natural and physical scientists. The outcomes of that workshop, lessons learned and opportunities missed, form the basis of this commentary, and they collectively indicate the barriers to integrating the natural, physical and social sciences on CDR. As the need for rapid, effective and successful CDR has only increased since that time, we argue that CDR researchers from across the spectrum must come together in ways that simultaneously address the technical, social, political, economic and cultural elements of CDR development, commercialization, adoption and diffusion if the academy is to have a material impact on climate change in the increasingly limited window we have to address it.